Output voltage tracking controller embedding auto-tuning algorithm for DC/DC boost converters - Choi, Kyunghwan; Kim, Yonghun; Kim, Kyung-Soo; Kim, Seok-Kyoon (IET power electronics, 2019)
This study suggests a non-linear output voltage tracking controller for DC/DC boost converters in the form of a classical cascade control structure. Non-linearities in the converter dynamics as well as parameter uncertainties and load variations are considered. The first contribution of this study is the design of an auto-tuner, which automatically adjusts the control gain according to the output voltage error to enhance transient performance. The second contribution involves proving that the closed-loop system ensures the performance recovery without any steady-state errors in the presence of parameter and load variations. The effectiveness of the proposed algorithm was verified through experimental investigations using a 5 kW prototype DC/DC boost converter.